Retinopathy of prematurity as a clinical marker of developmental vulnerability in preschool children: A nationwide Korean Health Screening study - Tae-Eun Kim; Hye Won Park; Sanghyun Park; Hyun Jin Shin (PLOS One, 2026)
Purpose To determine the Retinopathy of prematurity (ROP) and its association with developmental delay in Korean preschool children. Methods We conducted a nationwide cohort study using the Korean National Health Insurance Service and National Health Screening Program for Infants and Children (NHSPIC). The study included 808,536 children born 2014–2018 who completed the 7th NHSPIC screening at 54–60 months. Development assessed by the Korean Developmental Screening Test (K-DST) in six domains (self-care, cognition, language, fine motor, gross motor, and sociality. Subnormal visual acuity (VA) was defined as